Wheat Crop Productivity in the Mungbean – Wheat Cropping System in Rainfed Area of Potohar Pakistan (SAARC Journal of Agriculture, 2023)
Crop rotations have always a vital role in balancing of inter crops nutritional management, inhibiting of soil degradation, reduction of biotic and a biotic stress and in adapting to climate change. Potohar region is divided into three distinct rainfall zones i.e. high rainfall (>750 mm of annual rainfall), medium (500 to 750 mm) and low rainfall (